2006
DOI: 10.1158/0008-5472.can-06-1951
|View full text |Cite
|
Sign up to set email alerts
|

Presence ofEpidermal Growth Factor ReceptorGene T790M Mutation as a Minor Clone in Non–Small Cell Lung Cancer

Abstract: The threonine-to-methionine substitution at amino acid position 790 (T790M) of the epidermal growth factor receptor (EGFR) gene has been reported in progressing lesions after gefitinib treatment in non-small cell lung cancer (NSCLC) that causes sensitive tumors to become resistant to gefitinib. Alternatively, the EGFR T790M mutation might be present in small fractions of tumor cells before drug treatment, and the tumor cells harboring the T790M mutation might be enriched during the proliferation after drug tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
273
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(283 citation statements)
references
References 20 publications
6
273
2
2
Order By: Relevance
“…The reported double mutations (13)(14)(15)(16)(17)(18) generally involve a common activating mutation such as L858R and a rare mutation such as T790M. Concomitant T790M and L858R mutations confer gefitinib resistance in NSCLC patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The reported double mutations (13)(14)(15)(16)(17)(18) generally involve a common activating mutation such as L858R and a rare mutation such as T790M. Concomitant T790M and L858R mutations confer gefitinib resistance in NSCLC patients (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, direct sequencing could fail to detect mutated subclones (Pao and Ladanyi, 2007). Some EGFR-mutated subclones were already detected in NSCLC when EGFR T790M mutations have been analysed with sensitive techniques (Inukai et al, 2006). It was suggested that the possible presence of such mutations at a low frequency in NSCLC tumours before EGFRtargeted therapy might affect the tumour response or the eventfree survival after targeted treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In tumours from patients not treated with TKI, T790M appears to be rare, approximately 0.5% . The possibility exists, however, that this second mutation might be present at a low frequency at the time of diagnosis and that tumour cells harbouring this mutation might be enriched over time during treatment with gefitinib (Inukai et al, 2006).…”
Section: Resistance To Egfr-tkimentioning
confidence: 99%